Quality of financial reporting: approaches to measuring - Renkas, Jurij; Goncharenko, Olena; Lukianets, Olena (International Journal of Accounting and Economics Studies, 2015)
Financial reporting must meet many criteria to be considered high quality because it is the quality of information that determines the viability of future strategic decisions. The article investigates the essence of the concept of "quality" and "quality of financial infor-mation", and defines indicators and criteria of the financial reporting quality. As for the quality of the financial reporting, it is found that the latter is a structured reflection of financial condition and financial results of the entity, therefore, can be regarded as a set of components: quality of the financial information; quality of presentation of the financial information. It was found that the quality of the reporting of financial information is evaluated using a system of indicators that are qualified by the Financial reporting framework as the qualitative characteristics of useful financial information and National Accounting Statement (standard) 1 as the qualitative characteristics of financial reporting. In terms of formalization (presentation within the legislation forms) of the financial information presentation in Ukraine, we can speak of quality only in respect of the notes to the financial statements. It has been established that quality assessment indicators of presenting the financial information in the notes may be: readability of the information, visualization of the representation. Research of the quality requirements for the financial statements (information) of the participating countries of the former Soviet Union has identified many variations, but the most commonly used features are relevance, reliability, comparability and understandability. It is indicated that most post-Soviet countries, including Ukraine, gradually bring its legislation on the regulation of financial statements in conformity with IFRS. But there are still many unresolved differences, chief among which are the qualitative characteristics of the financial statements that should provide the information needs of different user groups.